Financial Report Performance Analysis of PT. Taspen Life Using Common Size and Trend Analysis Methods for 2022–2024 - Sulfiana; Wahdaniar Amir; Wijhah (CV Edujavare Publishing, 2026)
This study aims to determine the performance of financial reports at PT. Taspen Life for the period 2022-2024. This study uses the common size and trend method. Where the common size and trend methods are several ways to measure the proportion of each component and the company's financial performance. The research method used in this study is descriptive quantitative. The data collection techniques carried out by the researcher are documentation and data obtained from the annual report of PT. Taspen Life. Analysis using Common Size in the financial statements of PT. Taspen Life is reviewed from the company's balance sheet report consisting of assets, liabilities, and equity. The results show that the company's total assets have increased, the company's liabilities have fluctuated, namely an increase in 2023, then decreased in 2024. Meanwhile, the company's equity increased in 2023 and decreased again in 2024. When viewed from the trend analysis, assets and liabilities increased in 2024 while the company's equity decreased in 2024. Then the results of the analysis using Common Size in the financial statements of PT. Taspen Life's income statement shows a decline in revenue due to reduced premium income and other income, while expenses also decreased. A trend analysis of the company's income statement shows an increase in current year profit due to increased income from the company's investment returns.